An assessment of the ‘PHC Facility Governance Structures Trainer-of-Facilitator Learning Programme’ in Nkangala District, Mpumalanga Province - Esau, Natasha (Department of Public Health and Family Medicine, 2019)
Background In South Africa, as part of specified governance requirements, clinic committees were established to provide management oversight at Primary Health Care facilities. In order for them to better understand their roles they needed training. Facilitators in the district were selected to participate in the 'PHC Facility Governance Structures Trainer-of-Facilitator (ToF) Learning Programme’ in order to train the clinic committees. This study assessed the training of facilitators. Methods This retrospective single case study used qualitative methods and was guided by the Illuminative Evaluation Framework. It assessed whether the aims, objectives and methodology of the training programme was clearly conveyed by the trainers, whether this was understood by the participants and whether the participants were able to transfer the training programme as intended to the clinic committees. Qualitative data were collected through key informant interviews and focus group discussions, face to face and telephonically. These were complimented by a document and literature review. Study participants were purposively selected based on their involvement in the development, facilitation or training of the programme. Interviews were conducted in English, with semi-structured open ended questions pertaining to participants’ perceptions and understanding of the training, and whether the ToF Learning Programme was delivered to the clinic committees. After participants signed consent forms interviews were audio recorded and transcribed verbatim. Data analysis was done manually and guided by the methodology presented by Ritchie and Lewis. Results